2020
DOI: 10.1182/blood.2020004974
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIA expression accelerates nephritis and increases platelet activation in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease characterized by deposits of immune complexes (IC) in organs and tissues. The expression of FcγRIIA by human platelets, which is their unique receptor for IgG antibodies, positions them to ideally respond to circulating IC. Whereas chronic platelet activation and thrombosis are well-recognized features of human SLE, the exact mechanisms underlying platelet activation in SLE are still unknown. Here, we evaluated the involvement of FcγRIIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 76 publications
0
33
0
Order By: Relevance
“…FCGR2A , formerly known as CD32, plays an important role in the clearance of immune complexes by phagocytic cells such as macrophages and neutrophils. Prior studies have demonstrated strong evidence that FCGR2A is not only involved in immune system activities but also with autoimmunity ( 17 , 18 ). Based on the above findings, we can infer subtype 1 may be related to an autoimmune response targeting bile ducts which result into BA.…”
Section: Discussionmentioning
confidence: 99%
“…FCGR2A , formerly known as CD32, plays an important role in the clearance of immune complexes by phagocytic cells such as macrophages and neutrophils. Prior studies have demonstrated strong evidence that FCGR2A is not only involved in immune system activities but also with autoimmunity ( 17 , 18 ). Based on the above findings, we can infer subtype 1 may be related to an autoimmune response targeting bile ducts which result into BA.…”
Section: Discussionmentioning
confidence: 99%
“…SLE is an autoimmune disease that is characterized by the production of autoantibodies and multiorgan damage, especially nephritis 30‐32 . Previous studies have shown that Dex is able to reduce ANA and anti‐dsDNA antibody levels in MRL/lpr mice 29 .…”
Section: Discusionmentioning
confidence: 99%
“…The seed node of this cluster is FCGR2A (also known as FcγRIIA), which is expressed in human platelets. The expression of FcγRIIA by transgenic technology in lupus mice can trigger major changes in the platelet transcriptome and cause lung and kidney thrombosis 39 . Cluster 4 contains 26 nodes and 104 edges, with a score of 8.16.…”
Section: Resultsmentioning
confidence: 99%